2005
DOI: 10.2174/1381612054065783
|View full text |Cite
|
Sign up to set email alerts
|

Role of Anti-Oxidants in Atherosclerosis: Epidemiological and Clinical Update

Abstract: Low density lipoprotein (LDL) oxidative modification in the vascular wall seems to be a key factor in atherosclerosis development. Oxidised LDLs might recruit monocytes and favour their transformation into foam cells through a receptor-mediated intake (scavenger pathway). Moreover oxidised LDLs show cytotoxic potential which is probably responsible for endothelial cell damage and macrophage degeneration in the atherosclerotic human plaque. Following the oxidation hypothesis of atherosclerosis the role of natur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
63
0
4

Year Published

2006
2006
2013
2013

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 106 publications
(71 citation statements)
references
References 150 publications
3
63
0
4
Order By: Relevance
“…These studies support the epidemiological findings that carotenoid-containing foods may be beneficial in reducing the risk of CVD (59) . However, they suggest that their mode of action may not be entirely a result of their antioxidant properties.…”
Section: Carotenoids: Flavonoids: Cvd: Laser Doppler Imagingsupporting
confidence: 87%
“…These studies support the epidemiological findings that carotenoid-containing foods may be beneficial in reducing the risk of CVD (59) . However, they suggest that their mode of action may not be entirely a result of their antioxidant properties.…”
Section: Carotenoids: Flavonoids: Cvd: Laser Doppler Imagingsupporting
confidence: 87%
“…In general, dietary antioxidants may provide interactive or synergistic effects on health rather than any one food could not provide. The food groups and items selected in the present study contain a wide range of antioxidants such as flavonoids (including isoflavones and catechins), b-carotene, and vitamins C and E, and their antioxidant activity appears to be the result of a combination of those different compounds acting in a synergic and interactive manners (Jialal and Fuller, 1995;Honore et al, 1997;Bates et al, 1998;Williams and Clarkson, 1998;Wakai et al, 1999;Schutte et al, 2004;Cherubini et al, 2005).…”
Section: Resultsmentioning
confidence: 99%
“…Antioxidants can prevent cell damage due to the action of reactive oxygen species (ROS) and free radicals. 17 Honey contains a variety of falconoid and phenolic acids, which act as antioxidants, scavenging and eliminating free radicals. The researchers found that consuming more honey increased the level of polyphenolic antioxidants in the blood.…”
Section: Discussionmentioning
confidence: 99%